Trends of suicidal hanging in Western Mumbai region - Sonawane, Sachin S.; Sukhdeve, Rajesh B. (International Journal of Advances in Medicine, 2019)
Background: The present study was conducted with aims to determine various epidemiological factors of death due to hanging in the western Mumbai region and variation in types of hanging deaths. Methods: Four year study conducted at H. B. T. Medical College & cooper Hospital, Mumbai for period of January 2015 to December 2018. During study period total 6338 of medico-legal autopsies were conducted, of which 228 (3.59%) autopsies were of death due to hanging. Results: T228 out of 6338 medicolegal autopsies were of death due to hanging making incidence rate 3.59 % of hanging. Age group most commonly involved in hanging was 21-30 years constitutes 41.22% cases of hanging deaths. Male victims constitute of 59.64% cases and female victims were 40.36% cases. In 96.5% cases place of hanging was closed place inside room 3.5% cases hangings takes place in open place. Most common ligature material used for hanging was dupatta/odani constitute 46.5% cases followed by rope in 20.17% cases. Conclusions: Young age group population between 21-40 years are more susceptible victims of suicides by hanging constitute 65.78% cases. Proper parental and social guidance and support could prevent suicides in this age group. Timely counselling of such vulnerable group victims could preventable. Effective prevention strategies are needed to promote awareness of prevention of suicides in young age group.